SCIENCE TEACHERS’ CAPABILITY IN WRITING SYLLABUS IN ENGLISH VIEWED FROM KTSP 2006 AT INTERNATIONAL STANDARDIZED SCHOOLS (English Education Journal, 2012)
Penelitian ini bertujuan untuk mengamati secara teliti dokumen-dokumen guru tentang alat pembelajaran dan untuk mengukur kesulitan yang dialami dalam menulis silabus, terutama bagi guru non-Inggris. Berdasarkan permasalahn tersebut, untuk meningkatkan kemampuan dalam penyusunan dokumen khususnya silabus. Guru sains (fisika, kimia, dan biologi) dituntut untuk mendesain silabus dalam Bahasa Inggris, dimana itu menjadi masalah buat mereka. Dari penelitian ini ditemukan bahwa guru sains sudah dapat membuat dokumen tersebut dengan baik hanya saja masih mengalami kesulitan dalam produksi kalimat, pemilihan diksi, dan penggunaan grammar. Penguasaan dalam membuat silabus dengan Bahasa Inggris adalah salah satu syarat untuk mencapai proses instruksional yang berkualitas untuk mencapai kompetensi dasar siswa terutama pada Sekolah Berstandar Internasional.The aim of this study is to observe critically on the teachers’ document of  teaching-learning equipments and to find out the difficulties in writing syllabus in English, especially for non-English teachers. Therefore, it can improve the teachers’ ability in designing documents especially syllabus. Science teachers (Physics, Chemistry, Biology) should design their teaching-learning syllabus in English otherwise, it will cause serious problems for them. From the study, it was found out that the science teachers had performed good syllabus but they still meet some difficulties in using English for their teaching-learning documents, especially in producing sentences, choosing the vocabularies and the use of grammar. The teachers’ mastery in designing teaching-learning documents in English appropriately is one of the requirements to gain success in carrying on qualified instructional process and accomplishing students’ basic competence, especially in international standardized schools.